THE USE OF E-LKPD TO IMPROVE THE STUDENTS READING COMPREHENSION IN NARRATIVE MATERIALS - Saputra, Andika; Ithriyah, Siti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study examines the effectiveness of E-LKPD learning media in improving the learning outcomes of Grade XI students at SMAN 106 Jakarta. The study involved two classes of 36 students each, selected through purposive sampling. The results show that the experimental class using E-LKPD learning media showed significant improvement in learning outcomes compared to the control class using conventional methods. The experimental class showed a more consistent and homogeneous improvement, with the E-LKPD media helping students to better understand the material, increasing active participation and enabling a more engaged and interactive learning process. In addition, the flexibility of e-LKPDs to provide anytime, anywhere access to learning materials and the ease with which teachers can deliver content and monitor progress contributed to success. This study concludes that e-LKPDs are a significant and effective tool for improving student learning outcomes.